Future energy scenarios of household in Bhaktapur District - Bajracharya, Yogesh (Journal of Science and Engineering, 2015)
Energy plays a pervasive and critically important role in economic and social development. So, energy planning is important area of study. For Bhaktapur district energy plan, the survey was done by using the questionnaire. Total of 91 samples from rural area and 112 samples from urban area were taken to prepare primary database. The total energy demand was 952 TJ in rural area and 458 TJ in urban area in 2013. LEAP (Long-Range Energy Alternative Planning System) software was used for energy planning. Five scenarios, Business as Usual (BAU), Reference (REF), Accelerated Growth Rate (ACC), and Sustainable Energy for All (SE4ALL) in REF and ACC case scenarios were developed. Total energy demand in 2030 will be 2,748 TJ for BAU, 3,799 TJ for REF and 6,203 TJ for ACC case whereas total demand limits from 766 TJ and 1,241 TJ in SE4ALL scenario in REF and ACC case respectively. Again the total energy demand for 2045 will be 4,945 TJ, 9,104 TJ and 22,592 TJ for BAU, REF and ACC case respectively. Total energy demand for SE4ALL scenario will be 1,807 TJ and 4,381 TJ for REF and ACC case respectively. The GHG reduction up to 2045 by SE4ALL approach is 1.79 million metric tons of CO2 equivalent in REF and 3.54 million metric tons of CO2 equivalent in ACC Scenario.